A kappa opioid receptor agonist, difelikefalin, improves acute kidney injury in experimental sepsis models - Yoshiharu Sawanobori; Daisuke Nakano; Hiroaki Kitamura; Kento Kitada; Takehiko Asaga; Norio Suzuki; Masayuki Yamamoto; Yuichi Ogino; Gotaro Shirakami; Akira Nishiyama (PLoS ONE, 2026)
There is a pressing need for therapies that can lessen the severity of acute kidney injury (AKI) and subsequent critical illness. Difelikefalin, a peripherally acting kappa opioid receptor agonist, shows promise in controlling postoperative pain and chronic kidney disease-associated pruritis. Here, we report that difelikefalin attenuated AKI in experimental mouse models of critical illness. Preconditioning with difelikefalin significantly reduced oliguria in both lipopolysaccharide (LPS)-induced and cecum ligation and puncture-induced models. Moreover, difelikefalin treatment after renal ischemia/reperfusion substantially decreased the LPS-induced mortality rate on day 6 post-ischemia/reperfusion. We hypothesized that the reno-protective effects of difelikefalin are mediated through receptors expressed in either the neural system, immune cells, or the renal parenchyma. Denervation of nerves around the renal pedicle improved urine flow; difelikefalin further enhanced this improvement, regardless of renal denervation. Difelikefalin did not affect plasma cytokine levels after LPS administration at 3 and 6 hours. Renal kappa receptor expression overlapped with the pattern of neural crest-derived interstitial cells. LPS administration tended to increase cytokine expression in isolated renal kappa receptor-positive cells, and difelikefalin suppressed these changes. Overall, difelikefalin demonstrated renal protective effects against AKI in murine endotoxemia and polymicrobial sepsis models and improved survival in post-ischemia/reperfusion endotoxemia.